A Decision-Centric Approach to Risk Management in Aviation Stock Investments Using Value at Risk and Portfolio Optimization - Singagerda, Faurani Santi; Pratama, Muh. Riyaldi; Alfairus, M. Qodri; Iskandar, Akbar; Mamadiyarov, Zokir (PT Mattawang Mediatama Solution, 2025)
This study applies Monte Carlo simulation to analyze and compare the Value at Risk (VaR) of two Indonesian airline stocks—PT Garuda Indonesia (full-service carrier) and PT AirAsia Indonesia (low-cost carrier)—using daily return data from January to December 2023. The research examines risk-return characteristics at individual stock and portfolio levels across different confidence intervals (99%, 95%, and 90%). Results reveal that PT Garuda Indonesia exhibits higher expected returns (0.5168%) but also higher volatility (3.5980%) compared to PT AirAsia Indonesia (0.2412% return, 2.4868% volatility), reflecting their different business models. Remarkably, an equal-weight portfolio demonstrates extraordinary diversification benefits, with positive VaR values across all confidence levels, indicating robust downside protection even in adverse market conditions. At 99% confidence, the monetary VaR for a Rp100,000,000 investment shows potential maximum losses of Rp7,984,331 for Garuda and Rp5,460,951 for AirAsia, while the portfolio generates a minimum gain of Rp1,886,373. This study highlights the effectiveness of Monte Carlo VaR in capturing complex risk dynamics, demonstrates significant intra-sector diversification benefits challenging conventional diversification wisdom, and provides insights into how different airline business models translate into distinctive risk-return profiles. These findings have important implications for investment decision-making and risk management in specialized industry contexts, particularly in emerging markets.